Bottom-up synthesis and structural design strategy for graphene quantum dots with tunable emission to the near infrared region. (February 2019) - Huang, Dapeng; Zhou, Haifeng; Wu, Yaqiang; Wang, Tao; Sun, Leilei; Gao, Peng; Sun, Yuzhen; Huang, Huining; Zhou, Guangjun; Hu, Jifan
Abstract: Despite recent advances in the fabrication of graphene quantum dots (GQDs) with excellent fluorescence performance, it has been challenging to extend the fluorescence emission to deep red and short wave near-infrared. Herein, we present a strategy to reach the goal via hydrothermal treatment of polythiophene derivatives which mainly comprises a polythiophene conjugate skeleton, lots of benzene ring structure and alkyl chain. This structure is thermally converted into a doped crystalline GQDs at 170 °C for 20 h with the maximum fluorescence emission at 700 nm. In addition, the length of alkyl chain also has a regulatory effect on emission wavelength of final products, which enables the chemical molecular-level structural design of GQDs with specific light emission waveband. Graphical abstract: Image 1